Building Public Trust Through Social Media Political Communication and Government Image - Rifki, Muhamad; Basit, Abdul (Communication, 2026)
Research on government political communication on social media has predominantly focused on electoral contexts, with limited empirical attention to disaster management in developing countries, where crisis communication plays a critical role in sustaining public trust. This study examines the influence of government political communication exposure through social media on public trust during disaster management in Sumatra in 2025, with government image positioned as a mediating variable. Adopting a quantitative explanatory design, data were collected through an online survey of 250 active social media users who had been exposed to government disaster-related content. Data were analyzed using multiple regression and mediation analysis with a bootstrapping approach. The results demonstrate that exposure to government political communication on social media has a positive and significant effect on public trust and a significant effect on government image. Furthermore, mediation analysis confirms that government image partially mediates the relationship between political communication exposure and public trust. These findings indicate that the effectiveness of digital political communication in disaster contexts is not determined solely by message frequency, but by its capacity to construct a credible, competent, and responsive government image. This study contributes empirically to the literature on digital political communication and crisis communication by advancing a stimulus-image-trust model, highlighting the central role of government image in shaping public trust during large-scale disasters.